Drug resistance patterns of Klebsiella pneumonia strains isolated from Shaoxing City, Zhejiang Province in 2019: a multi-centre retrospective study. Issue 1 (31st December 2022) - Liang, Meichun; Mao, Guofeng; Zhang, Xiaojiao; He, Qiuli; Ying, Qunhua; Wang, Sheliang; Jin, Faxiang; Dong, Su; Lin, Xiuqin; Ruan, Yongchun; Li, Minghui; Lv, Li; et al.
Abstract : We retrospectively collected drug susceptibility data of Klebsiella pneumoniae from six tertiary hospitals in Shaoxing City in 2019 and performed a comparative analysis of drug resistance among different hospitals, sexes, ages, and specimens. In total, 1954 strains were identified. The antibiotic resistance rate varied from 4.42% to 36.18%. Most K. pneumoniae were still susceptible to carbapenems and tigecycline, with resistance rates of less than 10%. Drug resistance was relatively mild in Shaoxing Traditional Chinese Medicine Hospital and Shaoxing Maternal and Children Health Hospital, but most severe in Affiliated Hospital of Shaoxing University. Specimens were primarily obtained from elderly and male patients, and the resistance rate increased with age. The specimens were mostly collected from the respiratory and urinary tracts. No carbapenem-resistant strains were collected in 112 isolates from patients under 20 years of age. The ratio of carbapenem-resistant K. pneumoniae isolates was highest in blood-isolated strains (23.86%), and that of extended-spectrum beta-lactamase positive strains was highest in non-blood-sterile body fluids (37.37%). The resistance spectrum of K. pneumoniae varied between hospitals in the same area. Elderly and male patients, non-sterile body fluids, and blood source strains should be seriously considered in empirical treatment. Highlights Prevention and control should be strengthened in hospitals with high rate of drug resistance. Strengthen screening of drug-resistant bacteria in specific populations. Transferred patients should be alerted to the bacterial drug resistance status.